Markers of upper airway inflammation associated with microbial exposure and symptoms in occupants of a water‐damaged building. Issue 5 (6th February 2013) - Akpinar‐Elci, Muge; White, Sandra K.; Siegel, Paul D.; Park, Ju‐Hyeong; Visotcky, Alexis; Kreiss, Kathleen; Cox‐Ganser, Jean M.
Abstract Background Water damage in buildings has been associated with reports of upper airway inflammation among occupants. Methods This survey included a questionnaire, allergen skin testing, nasal nitric oxide, and nasal lavage on 153 participants. We conducted exposure assessments of 297 workstations and analyzed collected dust for fungi, endotoxin, and (1 → 3)‐β‐D‐glucan to create floor‐specific averages. Results Males had higher levels of nasal inflammatory markers, and females reported more symptoms. ECP, IL‐8, and MPO were significantly associated with nasal symptoms, flu‐like achiness, or chills. Fungi and glucan were positively associated with blowing out thick mucus. Endotoxin was significantly associated with ECP in overall models, and with ECP, IL‐8, MPO, and neutrophils among non‐atopic females. Conclusions In this study, we documented an association between endotoxin and nasal inflammatory markers among office workers. The results of our study suggest that a non‐allergic response may contribute to symptoms occurring among occupants in this water‐damaged building. Am. J. Ind. Med. 56:522–530, 2013. © 2013 Wiley Periodicals, Inc.